2014
DOI: 10.1186/1472-6947-14-30
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of general practitioners’ views on protocol-driven eReferral in Scotland

Abstract: BackgroundThe ever increasing volume of referrals from primary care to specialist services is putting considerable pressure on resource-constrained health services while effective communication across fragmented services remains a substantial challenge. Previous studies have suggested that electronic referrals (eReferral) can bear important benefits for cross-organisational processes and patient care management.MethodsWe conducted 25 semi-structured interviews and 1 focus group with primary care providers to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Eleven studies evaluated the impact of an innovation in terms of delivery and engagement [31, 33, 37, 38, 40-43, 47, 50, 51, 53, 55, 59]. For instance, Bouamrane et al used NPT to interpret factors identified as facilitating and challenging the work of GPs during patient consultations, and to understand stakeholder perspectives on the implementation of a primary care e-referral system [34,35]. Seven studies used NPT prospectively to explore the behavioural change required ahead of implementation [34-36, 44, 46, 48, 52, 54, 60].…”
Section: To Aid Implementation Planningmentioning
confidence: 99%
“…Eleven studies evaluated the impact of an innovation in terms of delivery and engagement [31, 33, 37, 38, 40-43, 47, 50, 51, 53, 55, 59]. For instance, Bouamrane et al used NPT to interpret factors identified as facilitating and challenging the work of GPs during patient consultations, and to understand stakeholder perspectives on the implementation of a primary care e-referral system [34,35]. Seven studies used NPT prospectively to explore the behavioural change required ahead of implementation [34-36, 44, 46, 48, 52, 54, 60].…”
Section: To Aid Implementation Planningmentioning
confidence: 99%
“…In the UK, eHealth systems interoperability is becoming all the more important as the adoption of patient electronic medical records within primary care is now wide-spread. This situation now provides opportunities to transfer and share patient electronic information across organisation within the National Health Service (NHS) that were previously unimaginable with paper-based records [9][10][11][12][13]. The next integration challenges will thus consist in enabling secure and efficient information sharing with other health organisations (e.g.…”
Section: Interoperabilitymentioning
confidence: 99%
“…In developed countries, most of the clinical encounters take place in a primary care settings and hence family doctors are often the gate-keepers to data-rich, longitudinal patient records containing a wealth of information about patients' conditions and their evolution over-time [11]. Ethier et al present an interoperability framework called the Clinical Data Integration Model using an ontology to support data integration of heterogeneous primary care electronic repositories in order to support research activities (i.e.…”
Section: Focus Theme Overviewmentioning
confidence: 99%
“…This study was financed by a grant (5/95/4762 in January 13, 2015) provided by the research deputy of Tabriz University of Medical Sciences. We would like to thank all the participants of the study.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…For this reason, some countries have carried out several interventions to improve their referral systems and positive results have been obtained 12 . These results comprise items such as communication improvement between health service providers at different levels, knowledge management improvement, reduction of waiting time, documentation improvement, reduction of the offering of unnecessary specialized services, and increase of access to health services 13 .…”
Section: Introductionmentioning
confidence: 99%